Dampak Good Corporate Governance dan Kinerja Keuangan Terhadap Nilai Perusahaan - Fadli, Syahir; Amaliah, Alyani; Mariati, Mariati (Forum Kerjasama Pendidikan Tinggi, 2025)
This research examines how Good Corporate Governance (GCG) and financial performance affect public company value in Indonesia. The audit committee, commissioners, independent commissioners, management ownership, and institutional ownership measure GCG factors. ROA and ROE measure financial success. Tobin's Q measures firm value. The analytical approach is multiple linear regression with simultaneous and partial testing. The findings reveal that GCG and financial success jointly affect business value. The average ROA was 2.70 and ROE was 15.97, with a substantial standard deviation of 1.87 and 12.33. Average audit committee: 3.10, total board of commissioners: 3.82, independent commissioners: 0.41, management ownership: 0.06, institutional ownership: 0.49. Therefore, ROA, ROE, audit committee, number of board of commissioners, and institutional ownership increase firm value. Although independent commissioners and management ownership have little impact. The supervisory role and managerial skills are crucial to generating firm value in Indonesia